THE EFFECT OF INTEGRATED MARKETING COMMUNICATION AND SERVICE QUALITY ON CUSTOMER PURCHASE DECISION GOJEK GRESIK - SUBARI, SATWIKA MUJTABA ZUHRON (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to determine the effect of Integrated Marketing Communication (IMC) and Service Quality on purchasing decisions on Gojek users in Gresik. This study uses quantitative methods, the population is Gojek customers in Gresik. Sampling was carried out with the Roscoe formula which yielded a value of 30, furthermore, the accuracy of SPSS analysis using a value of 100. The data was obtained by questionnaires distributed in June 2018. There were 22 questions in the questionnaire with Likert scale. This study used multiple regression analysis by testing the validity and reliability testing for each statement. Hypothesis testing is applied in this study with F test, t-test, correlation coefficient, and determination coefficient. The classic assumption test in this study was applied using multicollinearity test, heteroscedasticity test, autocorrelation test, normality test, and linearity test. The results of this study shows that Integrated Marketing Communication variables and Service Quality variables simultaneously influence purchasing decisions. It can be concluded that increasing the independent variables, namely Integrated Marketing Communication and Service Quality, will also increase the dependent variable, namely the purchase decision for Gojek in Gresik. Keywords: Integrated Marketing Communication, Service Quality, Purchase Decisions